DETERMINAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Wahyuningsih, Devi; Trisnawati, Ema; Sukmawati, Taryati (Jurnal Ekonomi STIEP, 2023)
This study was conducted to analyze the effect of variable profitability ratios, liquidity ratios, size of firm, and independent commissioner of the timeliness for financial statements submission on Properties & Real Estate companies in Indonesia Stock Exchange (IDX) in 2020-2022.The population in this study is Properties & Real Estate companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique used was purposive sampling and obtained a sample of 180 companies. Statistical testing and data processing performed using logistic regression analysis. The results of this study showed that liquidity ratios had a positive effect on the timeliness of financial statement submission. Meanwhile, profitability ratios, company size and independent commissioners company do not effect the timeliness of financial statement submission.